Plants volume as a factor affecting outdoor ambient air and thermal condition - Omar, Siti Rahmah (2010)
This study evaluates the effectiveness of plants for outdoor ambient air and outdoor thermal improvement based on volume size. The growing conceptualization of green space is partly as a function that contributing towards a better environmental quality and maintenance of ecological system in urban area in giving evidence to sustainable urban living. However, the general requirement for plantings in designated urban green spaces is 4% from the whole development without reckoning the height or volume of the plants which should be considered in providing outdoor thermal comfort and clean air. Focusing on ambient air quality, this study quantify amount of carbon dioxide, oxygen, temperature and relative humidity influence by plants volume based on field data. Result shows that there is influence of plants volume in green space to the pattern of air chemical composition in an outdoor space. The study also concluded that the design and planning of green space should give more consideration on both the plants volume and area size especially in a tropical country like Malaysia, in order to enhance air quality and thermal comfort.